Keikutsertaan Masyarakat Dalam Pengembangan Lokal (Studi Kasus: Pengembangan Desa di Jawa Barat) - Sawitri, Dewi (Journal of Regional and City Planning, 2006)
Regional development practices, which adopted âSpatial Planning Systemâ concept, have been considered less effective and at the expense of underdeveloped regions. Therefore, underdeveloped regions empowerment has become a very important issue. The concept of Local Resources-based Regional Development has the potential as regional development practices reference. This concept emphasizes local empowerment and places local people as the key element in development, where local people are assigned a pivotal role in the regional development process through active participation. In rural West Java cases, Rural Development experiences have shown that Community Participation has improved rural development achievement. Community participation has not been affected by the distance of villages to the nearest town. The improving of community involvement system and shifting of village leaderâs mindset are the prerequisite of community participation enhancement.Keywords: regional development, community participation, local empowerment.